Analysis of the economic viability of organic production system of ornamental pineapple plants for cut stems - Pereira, Gabriella Navarro Donato; Souza, Everton Hilo de; Souza, José da Silva; Cardoso, Carlos Estevão Leite; Santos, Adenildo Bernardo dos; Souza, Fernanda Vidigal Duarte (Ornamental Horticulture, 2021)
The growth of Brazilian floriculture is remarkable, both in terms of the number of producers and the cultivated area. To reduce costs and add value, the organic production of ornamental pineapple plants is an option for some consumer markets. This study was carried at the Fundação José Carvalho, municipality of Entre Rios (Bahia State), Brazil, to evaluate the economic viability of the organic production of ornamental pineapple plants, as well as to analyze the economic factors from implantation of the crop to the final production phase. Primary and secondary data collection (technical coefficients and prices) was carried out, which allowed updating the value of these coefficients. After determining the technical coefficients, input prices and product prices were surveyed and were inserted in spreadsheets of production cost and profitability. Data processing and profitability analysis were carried out under deterministic and risk conditions. The organic cultivation system for ornamental pineapples proved to be economically viable, providing greater profitability and production of stems, which is the product of interest.